RNA binding proteins PTBP1 and HNRNPL regulate CFTR mRNA decay - Amna Siddiqui; Arpit Saxena; Joshua Echols; Viktoria Havasi; Lianwu Fu; Kim M. Keeling (Heliyon, 2023)
Background: CFTR nonsense alleles generate negligible CFTR protein due to the nonsense mutation: 1) triggering CFTR mRNA degradation by nonsense-mediated mRNA decay (NMD), and 2) terminating CFTR mRNA translation prematurely. Thus, people with cystic fibrosis (PwCF) who carry nonsense alleles cannot benefit from current modulator drugs, which target CFTR protein. In this study, we examined whether PTBP1 and HNRNPL, two RNA binding proteins that protect a subset of mRNAs with a long 3’ untranslated region (UTR) from NMD, similarly affect CFTR mRNA.Silencing RNAs were used to deplete PTBP1 or HNRNPL in 16HBE14o- human bronchial epithelial cells expressing WT, G542X, or W1282X CFTR. CFTR mRNA abundance was measured relative to controls by quantitative PCR. PTBP1 and HNRNPL were also exogenously expressed in each cell line and CFTR mRNA levels were similarly quantified. Results: PTBP1 depletion reduced CFTR mRNA abundance in all three 16HBE14o- cell lines; HRNPL depletion reduced CFTR mRNA abundance in only the G542X and W1282X cell lines. Notably, decreased CFTR mRNA abundance correlated with increased mRNA decay. Exogenous expression of PTBP1 or HNRNPL increased CFTR mRNA abundance in all three cell lines; HNRNPL overexpression generally increased CFTR to a greater extent in G542X and W1282X 16HBE14o- cells.Our data indicate that PTBP1 and HNRNPL regulate CFTR mRNA abundance by protecting CFTR transcripts from NMD. This suggests that PTBP1 and/or HNRNPL may represent potential therapeutic targets to increase CFTR mRNA abundance and enhance responses to CFTR modulators and other therapeutic approaches in PwCF.